On the ergodic theorem in the Kozlov–Treshchev form for an operator semigroup - Korolev, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study nonuniform ergodic averages of the Kozlov – Treshchev type for operator semigroups and obtain estimates for the corresponding maximal functions.